Analysis of the internal organizational communication process and its relationship with the satisfaction of the employees of a car dealership company in Piedras Negras Coahuila (GEON Journal (Management, Organizations and Business), 2020)
Communication within an organization is of the utmost importance since through it the strategies are deployed in order that all its workers reach the company objectives.The objective of this investigation is to analyze how this internal communication relates to the satisfaction of the employees and their superiors of the Piedras Negras Coahuila car dealership.This study is descriptive and correlational, a survey was used to collect the perceptions of all employees if the company.The result of the investigation shows that the employees are satisfied with the internal communication that takes place between the same colleagues as well as with their superiors
Keywords: Automotive; organizational communication; company; process; satisfaction